(untitled) (Journal of Mechanical Engineering, 2013)
The paper presents a numerical method for calculating a potential flow around a ship of transomstern with respect to the double-body potential. The method of solution is based on the distribution of Rankinesources on the hull as well as its image and on the free surface. An iterative algorithm is used for determiningthe free surface and wave resistance using Dawsons upstream finite difference operator. A verification ofnumerical modeling is made using NPL- 4A model and the validity of the computer program is examined byidentifying the transverse and diverging wave patterns of AMECRC model moving in infinite depth of water. DOI: http://dx.doi.org/10.3329/jme.v43i1.15766